Simulation and modelling for climate adaptation and mitigation. Experiences of environmental renovation in Rome - Fabrizio Tucci; Valeria Cecafosso; Paola Altamura; Marco Giampaoletti (Agathón)
This paper defines an original methodological and applicative approach in support of the experimental/planning phase in the area of the regeneration of urban districts, in order to offer responses to the challenges of adapting to and mitigating climate change. Applied in two case studies in Rome, the methodology incorporates and verifies strategies and passive bioclimatic solutions through activities of ex-ante/ex-post modelling/simulation, constructing multicriteria and multiscalar planning models based on fluid dynamics, and measuring their effectiveness through the quantification of the reduction of CO2 emissions. The expected results are improved environmental comfort in outdoor, in-between, and indoor spaces, lower energy demand and CO2 emissions mitigation, through a set of actions and solutions that are comparable, replicable, and measurable in terms of energy-climate performance and environmental well-being.